Ida B. Wells : Let the Truth Be Told - Myers, Walter Dean; Christensen, Bonnie (New York : Scholastic, 2008)
Award-winning author Myers tells the story of legendary civil rights figure Ida B. Wells, who fought to make the lives of African Americans better long before the events of the 20th century.
Keywords: African Americans -- non-fiction